1997
DOI: 10.1007/s11745-997-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugated linoleic acid on body composition in mice

Abstract: The effects of conjugated linoleic acid (CLA) on body composition were investigated. ICR mice were fed a control diet containing 5.5% corn oil or a CLA-supplemented diet (5.0% corn oil plus 0.5% CLA). Mice fed CLA-supplemented diet exhibited 57% and 60% lower body fat and 5% and 14% increased lean body mass relative to controls (P < 0.05). Total carnitine palmitoyltransferase activity was increased by dietary CLA supplementation in both fat pad and skeletal muscle; the differences were significant for fat pad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

60
792
8
72

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,050 publications
(932 citation statements)
references
References 30 publications
60
792
8
72
Order By: Relevance
“…Dietary CLA has been reported to reduce carcinogenesis (Ha et al 1987;Ha et al 1990;Pariza and Ha 1990;Ip et al 1991), atherosclerosis (Lee et al 1994), and body fat (Park et al 1997). Recently, similar effects were found for conjugated trienoic acids.…”
Section: Introductionmentioning
confidence: 82%
“…Dietary CLA has been reported to reduce carcinogenesis (Ha et al 1987;Ha et al 1990;Pariza and Ha 1990;Ip et al 1991), atherosclerosis (Lee et al 1994), and body fat (Park et al 1997). Recently, similar effects were found for conjugated trienoic acids.…”
Section: Introductionmentioning
confidence: 82%
“…5 The retroperitoneal fat pad results strongly support the established ability of CLA to reduce adipose store accumulation in mice without altering total body weight. 34,35 Each of the interventions containing CLA reduced the retroperitoneal fat pad weights compared to PLTR. In addition, CrM, which increases fat free mass, 35,53 and ␣-LA, which influences glucose and lipid metabolism, 8,17 also reduced visceral adiposity.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Each of the interventions containing CLA reduced the retroperitoneal fat pad weights compared to PLTR. In addition, CrM, which increases fat free mass, 35,53 and ␣-LA, which influences glucose and lipid metabolism, 8,17 also reduced visceral adiposity. Although the effects of CLA in humans remain controversial, two studies have found that CLA reduced body fat mass in overweight humans, 1,13 suggesting that it may be an adjunctive therapy for attenuating corticosteroid-induced fat gain in boys with DMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trans-10,cis-12 CLA also inhibits the expression of glucose transporter-4 (GLUT-4) 37,38 and increases the activity of carnitine palmitoyltransferase (CPT), enhancing fatty acid oxidation 10 . Trans-10,cis-12 CLA reduces lipogenesis in human 37 and mice adipocytes, decreasing sterol regulatory element-binding protein-1 (SREBP-1) expression in vivo 39 .…”
Section: Effects Of Conjugated Linoleic Acid On Adipocytesmentioning
confidence: 99%